Containers in Rockets: From Earth to Space – Bridging Technology and Society - Venkata Surya Sai Charan Lolla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the convergence of containerization technologies across information technology and aerospace domains, examining how standardization principles originally developed for software deployment have been adapted for space applications. It traces the parallel evolution of containerization in both fields, analyzing conceptual foundations, implementation challenges, socioeconomic implications, and future trajectories. The article reveals how standardized interfaces, modular architectures, and ecosystem development have enabled significant cost reductions, accelerated development cycles, and democratized access to space technologies. By examining case studies of successful technology transfers between digital and physical domains, the paper demonstrates how containerization facilitates innovation through improved interoperability and cross-domain knowledge diffusion, ultimately reshaping both technological landscapes through convergent principles despite their different physical manifestations.
Keywords: Containerization; Aerospace Standardization; Modular Systems; Technology Transfer; Space Commercialization